Gondolatok a szerzői jogi törvény legújabb módosítása kapcsán - Kiss, Tibor (Debreceni Jogi Műhely, 2006)
The Act LXXVI of 1999 on Copyright was amended by the Act CVLV of 2005 with effect of 15 April 2006 in compliance with the provisions of the Directive of the European Parliament and of the Council on measures and procedures to ensure the enforcement of intellectual property rights (hereinafter: “Enforcement-Directive”). The Enforcement-Directive concerns the measures necessary to ensure the enforcement of intellectual property rights (copyrights, patent, trade marks, etc.). The Member States of the European Union had to provide for the proportionate measures and procedures needed to ensure the enforcement of intellectual property rights covered by the Enforcement-Directive. The amended and supplement provisions of the Hungarian Act on Copyright provide efficient shelter for the authors from the infringement of copyright law on the one hand and provide legal (procedural) guarantees for the potential infringers on the other hand. There are some new provisions which can be applied against the infringers not only by final judgment but also as provisional and precautionary measures. When a judicial decision has been taken finding an infringement of copyright or neighbouring right, the judicial authorities may serve the infringer with an injunction aimed at prohibiting the continuation of the infringement. The judicial authorities can serve the alleged infringer, or the intermediary whose services are being used by a third party to infringe a right, with an interlocutory injunction intended to prevent any impending infringement of copyright or neighbouring right, or to forbid the continuation of the alleged infringements of copyright or neighbouring right, or to make such continuation subject to the lodging of guarantees intended to ensure the compensation of right holder. The judicial authorities can be empowered to require the applicant to provide any reasonably available evidence to their satisfaction with a sufficient degree of certainty that the applicant is the right holder and that the applicant’s right is being infringed or, that such infringement is imminent. The judicial authorities may order the publication or seizure of bank, financial or commercial documents. The judicial authorities may order the recall, at the infringer’s expense in appropriate cases, of the goods which have been found to infringe copyright or neighbouring right and may order that the goods which have been found to infringe the right, as well as the materials and implements used primarily for the creation or the manufacture of the goods in question, be disposed of outside the channels of commerce, without any compensation being due. It can be also ordered, that the decision be displayed and published in full or in part in the newspapers or in the internet designated by the right holder. The most efficient protection against the usurpation can be satisfied by the parallel regulation of the civil and criminal law. The next steps to be done by the European Union are the criminal law provisions. Besides the regulations, consistent jurisdiction is necessary, in which the courts should play an important role.